Apokalips Milik Siapa? Unfuturability dan Politik Futuritas Kolonial-Pemukim dalam Narasi Apokaliptik Barat - Ardana, Stefanus Galang (Sanata Dharma University, 2025)
This paper argues that reading Western settler-colonial apocalyptic narratives—including films, video games, and novels such as The Road, the Fallout series, Children of Men, and Interstellar—through the lens of unfuturability reveals their underlying political function. I distinguish between “apocalypse-as-genre,” the spectacular collapse imagined in these works, and “apocalypse-as-structure,” the slow violence already endured in places such as Sumatra, Kalimantan, and Papua. The analysis identifies three recurring settler-colonial tropes that work to secure the future as a racially exclusive domain: the reimagining of land as an emptied frontier, the rebirth of the hunter-hero through righteous violence, and the salvation of the future through a settler adoption fantasy. These tropes function as a form of “white property” by controlling who inherits futurity. In response, unfuturability is proposed as both an analytic and an ethic: a political refusal of the colonial future that opens space for plural, relational worlds already being built through Indigenous land stewardship, Black mutual aid, and decolonial archival practice. By using unfuturability to name and critique these narrative patterns, this paper offers a framework for reading apocalyptic culture beyond the horizons secured by settler futurity.